RESILIENCE COMMUNICATION OF UMKM ACTORS IN JEPARA CASE STUDY ON FAZA FURNITURE - Ahmad Rudyt Haidar; Lusy Mukhlisiana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the resilience communication strategy implemented by Faza Mebel, a micro-enterprise in the furniture sector in Jepara, in responding to the challenges of the COVID-19 pandemic. Using a qualitative approach and a single case study design, the research explores how internal and external communication practices are carried out to build business resilience. Buzzanell’s (2010) Resilience Communication Theory serves as the main analytical framework, covering five dimensions: crafting normalcy, affirming identity anchors, maintaining communication networks, putting alternative logics to work, and legitimizing negative feelings while foregrounding productive action. The findings reveal that Faza Mebel’s success in sustaining its business is not solely driven by digitalization, but also by a structured, participatory, and long-term communication strategy. This study contributes theoretically to the development of organizational communication studies in the context of MSMEs and offers practical recommendations for micro-business actors to face crises through resilient and adaptive communication aligned with market changes.